Transcriptomic Analysis of Young and Old Erythrocytes of Fish - Götting, Miriam; Nikinmaa, Mikko J. (Frontiers in Physiology, 2017)
Understanding gene expression changes over the lifespan of cells is of fundamental interest and gives important insights into processes related to maturation and ageing. This study was undertaken to understand the global transcriptome changes associated with ageing in fish erythrocytes. Fish erythrocytes retain their nuclei throughout their lifetime and they are transcriptionally and translationally active. However, they lose important functions during their lifespan in the circulation. We separated rainbow trout (Oncorhynchus mykiss) erythrocytes into young and old fractions using fixed angle-centrifugation and analyzed transcriptome changes using RNA sequencing (RNA-seq) technology and quantitative real-time PCR. We found 930 differentially expressed between young and old erythrocyte fractions; 889 of these showed higher transcript levels in young, while only 34 protein-coding genes had higher transcript levels in old erythrocytes. In particular genes involved in ion binding, signal transduction, membrane transport, and the activities of those encoding various enzyme classes are impaired affected in old erythrocytes. The transcripts with higher levels in old erythrocytes were associated with 7 different GO terms within biological processes and 9 within molecular functions and cellular components respectively. Our study furthermore found several highly abundant transcripts as well as a number of differentially expressed genes for which the protein products are currently not known revealing the gaps of knowledge in most non-mammalian vertebrates. Our data provide the first insight into pathways changes involved in ageing on the transcriptional level and thus opens new perspectives for the study of maturation processes in fish erythrocytes.